Relative Distribution of Refractive Errors: An Audit of Retinoscopic Findings - Khawaja Sharif-ul-Hassan, Muhammad Zia-ul-Haque Ansari, Abrar Ali, Adnan Afaq, Tabassum Ahmed (Pakistan Journal of Ophthalmology, 2007)
Purpose: To observe the relative distribution of refractive errors in the mixed ethnic population of Karachi and review the current concepts into the pathophysiology of refractive errors. Material and Methods: We retrospectively analyzed the retinoscopic findings of 1924 eyes of 962 patients presenting with refractive problems from January 1984 to December 1991 to determine their refractive status. Refraction was performed objectively on all patients by one of us (KSH) using streak retinoscope. Sphero-cylindrical method of refraction was used to minutely neutralize the reflex. Subsequently, retinoscopic findings were subjectively verified. Half-diopter cross cylinder was used to verify and refine the power and axis of any cylindrical lens. Any error, stigmatic (spherical) or astigmatic (cylindrical), of ¼-diopter or more was considered an error and included in the analysis. Result: Astigmatism was the most common refractive error found in this retinoscopic analysis (914 of 1898 eyes; 48.16%) followed by myopia (894 of 1898 eyes; 47.10%) and hypermetropia (90 of 1898 eyes; 4.74%). Myopic error (stigmatic and astigmatic myopia combined) comprised the largest group among the analyzed population (1554 of 1898 eyes; 81.88%) followed by hypermetropic error (stigmatic and astigmatic hypermetropia combined) (265 of 1898 eyes; 13.96%) and mixed error (mixed astigmatism) (39 of 1898 eyes; 2.05%). Conclusion: Myopia and myopic astigmatism were the major refractive errors found in the mixed ethnic population of Karachi city in the age group from 1 to 40 years.